Modern Learning to Children Social Care Children Through the Suka Math Dasar Program - Ismaya Alya; Indy Kanaishia; Tanissa Mayra Tsabitha; Anggeline Wellvy Santoso; I Putu Juni Artana (IJRAEL: International Journal of Religion Education and Law, 2022)
Panti Sosial is a place where many children, especially underage, are placed because there is no supervision and attention from the nuclear family. This is what triggers teenagers to be lazy to study and feel insecure to feel ashamed to learn something new. Adolescents or children living in children's social institutions need as much attention and supervision from caregivers or friends as possible. But the hope of getting it cannot replace parents. The number of caregivers is not balanced which causes the sense of attention, support, and affection from caregivers to be less than optimal. Apart from that, teenagers or children who live in children's social homes come from different families, cultures, habits, and socialization processes. Therefore, the solution from the author is about how teenagers or children who are in children's social homes are able to hone their thinking skills through learning mathematics. By using the Casework method, it is hoped that from the project agenda offered so that children or adolescents in children's social institutions are able to find their identity and capacity, especially in mathematics lessons which have a strong connection with the world of education.